Metabolic Regulation of Insulin Secretion - Keane, Kevin; Newsholme, Philip (Academia Press, 2014)
Regulation of metabolic fuel homeostasis is a critical function of b-cells, which are located in the islets of Langerhans of the animal pancreas. Impairment of this b-cell function is a hallmark of pancreatic b-cell failure and may lead to development of type 2 diabetes mellitus. b-Cells are essentially “fuel sensors” that monitor and react to elevated nutrient load by releasing insulin. This response involves metabolic activation and generation of metabolic coupling factors (MCFs) that relay the nutrient signal throughout the cell and induce insulin biosynthesis and secretion. Glucose is the most important insulin secretagogue as it is the primary fuel source in food. Glucose metabolism is central to generation of MCFs that lead to insulin release, most notably ATP. In addition, other classes of nutrients are able to augment insulin secretion and these include members of the lipid and amino acid family of nutrients. Therefore, it is important to investigate the interplay between glucose, lipid, and amino acid metabolism, as it is this mixed nutrient sensing that generate the MCFs required for insulin exocytosis. The mechanisms by which these nutrients are metabolized to generate MCFs, and how they impact on b-cell insulin release and function, are discussed in detail in this article.